A Study on Job Satisfaction towards Dairy Farmers in Neyyattinkara Taluk of Trivandrum District (International Journal of Food and Nutritional Sciences, 2022)
One of the main areas of study for organisational behaviour and human resource management is job satisfaction. It displays how employees feel about their work and how committed they are to the company. Job satisfaction is the term used to describe how someone feels or is feeling about their employment. It conveys a person's level of satisfaction with their work. The term "job satisfaction" refers to a person's sense of fulfilment when working, which serves as a driving force to do so. It is not selfsatisfaction, happiness, or contentment, but rather job satisfaction. The happy emotional state that arises from the perception that one's work contributes to or facilitates the attainment of one's employment values is known as job satisfaction. The study aided in illuminating the degree of employee satisfaction in light of the numerous organisational aspects. The results of this study unequivocally demonstrate that workers in organisations are generally content with their jobs. The company must to take into account factors like pay, the rapport between workers and managers, how complaints are handled, and how much opportunity it provides new hires.